Media Sosial TikTok Dalam Membangun Citra Diri: (Analisis Teori Dramaturgi dan New-Media) - Mutia Tisa (Seutia Hukamaa Cendekia, 2023)
Tiktok, as a feature on social media applications, has become a phenomenon involving many users in contemporary society. This platform is not just a functional space for interaction and information-seeking; it has also shifted into a symbol of self-image and lifestyle. Symbolic interactionism and consumer society theories can encapsulate this phenomenon, where TikTok is not merely a gathering place but also a stage for expressing, actualizing, and shaping one's self-image. In this context, personal branding emerges as an effort to cultivate a positive image and attract the attention of others. TikTok users actively portray themselves by posting photos and videos to create a positive impression and garner public attention. Despite the gap between social media life and real life, users are willing to purchase likes and followers to maintain their popularity. Thus, the phenomenon of TikTok usage can be analyzed through the perspectives of Darmatugi's theory and new media, especially the theory of use and gratification.